2009
DOI: 10.1158/1078-0432.ccr-08-3206
|View full text |Cite
|
Sign up to set email alerts
|

Visualizing Implanted Tumors in Mice with Magnetic Resonance Imaging Using Magnetotactic Bacteria

Abstract: Purpose To determine if magnetotactic bacteria can target tumors in mice and provide positive contrast for visualization using magnetic resonance imaging. Experimental Design The ability of the magnetotactic bacterium, Magnetospirillum magneticum AMB-1 (referred to from here as AMB-1), to confer positive magnetic resonance imaging contrast was determined in vitro and in vivo. For the latter studies, AMB-1 were injected either i.t. or i.v. Bacterial growth conditions were manipulated to produce small (~25-nm … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
77
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 107 publications
(82 citation statements)
references
References 33 publications
(30 reference statements)
4
77
0
1
Order By: Relevance
“…100 A drawback is its low sensitivity: approximately micromolar concentrations of an imaging probe can be detected within a given voxel (10 À 3 -10 À 5 mol/l) which is three to six orders of magnitude lower than the sensitivity of optical imaging for detection of fluorochromes in vivo. 101 Benoit et al 102 exploited the innate physiology of magnetotactic bacteria to target tumors in mice and provide positive contrast for visualization using MRI. The ability of Magnetospirillum magneticum AMB-1 to confer positive MRI contrast was determined both in vitro and in vivo.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
See 1 more Smart Citation
“…100 A drawback is its low sensitivity: approximately micromolar concentrations of an imaging probe can be detected within a given voxel (10 À 3 -10 À 5 mol/l) which is three to six orders of magnitude lower than the sensitivity of optical imaging for detection of fluorochromes in vivo. 101 Benoit et al 102 exploited the innate physiology of magnetotactic bacteria to target tumors in mice and provide positive contrast for visualization using MRI. The ability of Magnetospirillum magneticum AMB-1 to confer positive MRI contrast was determined both in vitro and in vivo.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…The ability of Magnetospirillum magneticum AMB-1 to confer positive MRI contrast was determined both in vitro and in vivo. 102 The strain was administered to tumor bearing mice either intra-tumorally or intravenously and tumor targeting was confirmed using a multiple of approaches including 64 Cu-labeled bacteria. Significantly M. magneticum with small magnetite particles generate T1-weighted positive contrast, enhancing in vivo visualization by MRI.…”
Section: Magnetic Resonance Imagingmentioning
confidence: 99%
“…In addition to synthetic iron oxide nanoparticles, the use of magnetosomes (MNs) in biomedicine has also been recently proposed (8,9). These nanostructures, constituted by pure magnetite particles arranged in chains and surrounded by a phospholipid membrane (10,11), are naturally synthesized by magnetotactic bacteria under specific environmental conditions.…”
Section: Introductionmentioning
confidence: 99%
“…Benoit et al reported that the magnetotactic bacteria Magnetospirillum magneticum AMB-1 could produce positive MRI contrast and colonize mouse tumor xenografts, providing a potential tool for MRI visualization of bacteria in preclinical and translational studies to track cancer despite its lower sensitivity. Following IV injection of 64 Cu-labeled AMB-1, PET imaging also revealed increased bacterial colonization of tumors, but decreased colonization of other organs, such as liver and spleen, after 4 h [57].…”
Section: Bacteriamentioning
confidence: 99%